Neotropical biodiversity: timing and potential drivers - Rull, Valentí (Trends in ecology & evolution (Amsterdam), 2011)
The origin of extant neotropical biodiversity has been a controversial topic since the time of Darwin. In this review, I discuss the timing of, and potential driving factors associated with, diversification using recent evidence from molecular phylogenetics. Although these studies provide new insights into the subject, they are sensitive to dating approaches and targets, and can eventually lead to biased conclusions. A careful analysis suggests that the origin of extant neotropical biodiversity cannot be attributed to the action of one or few events during key time intervals. Rather, it is the result of complex ecological and evolutionary trends initiated by Neogene tectonic events and palaeogeographical reorganisations, and maintained by the action of Pleistocene climatic changes.